A dielectrically modulated electrically doped tunnel FET for application of label free biosensor. (September 2017) - Venkatesh, Pulimamidi; Nigam, Kaushal; Pandey, Sunil; Sharma, Dheeraj; Kondekar, P.N.
Abstract: The fabrication challenges and cost of nanoscale devices have been a major concern in the field of label free biosensor. Therefore, to overcome these issues, we report for the first time a dielectrically modulated electrically doped tunnel field-effect transistor (DM-EDTFET) as a biosensor for label free detection. For this purpose, n + drain and p + source regions in proposed device are induced by considering polarity bias of PG-1 = +1.2 V and PG-2 = −1.2, respectively over the ultra-thin silicon body. The proposed structure is immune against doping control issues, avoids thermal budget and fabrication complexity as compared to its counterpart TFET. In DM-EDTFET, a nanogap cavity embedded within the gate dielectric is formed by etching the selected portion of gate dielectric layer towards the source side for sensing the biomolecules. The sensing ability of DM-EDTFET has been analysed in terms of variation in dielectric constant and charge density of biomolecules, and device geometry parameters at different bias conditions. To analyse the relative sensitivity, proposed DM-EDTFET is compared with MOSFET based biosensor in terms of sensing parameters. From these results, DM-EDTFET provides superior results in terms of sensitivity as compared to MOSFET based biosensor. Hence, the proposed DM-EDTFET biosensor can be a promising candidate for the development of future sensing bio-equipments. Highlights: A nanogap cavity embedded DM-EDTFET based biosensor is proposed for the detection of biomolecules. Performance of the device is analyzed in terms of carrier concentrations, band diagrams, surface potential, electric field, drain current sensitivity, etc. Formation of p+ source and n+ drain regions are done by electrically doped mechanism instead of physical doping to achieve the concentration in the order of 10 19 cm −3 . Significant variation in sensitivity characteristics reflects the ability of DM-EDTFET to detect the charge in the nanogap cavity. Effect of device geometry parameters are also analysed.